Microwave Imaging Technique Using UWB Signal For Breast Cancer Detection - Mohd Salleh, Siti Hasmah; Othman, Mohd Azlishah; Ali, Nadhirah; Sulaiman, Hamzah Asyrani; Misran, Mohamad Harris; Abd Aziz, Mohamad Zoinol Abidin (Asian Research Publishing Network (ARPN), 2015)
Microwave Imaging modalities used for breast cancer detection currently are not sufficient for society’s need. The key features for microwaves technique for tumor detection by the observation at microwaves frequencies, the dielectric contrast of permittivity and conductivity between normal and malignant tissues. This project focuses on the experimental of reflection coefficient in complex frequency domain obtained using vector network analyzer transform into time domain using Inverse Fast Fourier Transform (IFFT). Breast phantom is illuminating from various points with short UWB microwave pulse generated by RF Horn antenna with frequency of 1GHz -10GHz and the collected backscattered energy is being analyzed and simulated using Microwave imaging algorithms to identify the presence and localization of the tumors.The experiment represent medium form by a rectangular shape of container filled with oil and small size of 3cm stone as a reflected target that represent as a malignant tissues in the breast sample.